The management of power in a warring state system: An evaluation of balancing, collective security and laissez-faire policies - Thomas R. Cusack (Wissenschaftszentrum Berlin für Sozialforschung (WZB); Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1988)
Realist and Idealist prescriptions for the management of power in a multistate system are described and their implications for system preservation and state survival are examined. The examination of these competing or alternative foreign policy styles is carried out through an experimental study using a large-scale computer simulation model. The results of the analysis tend to highlight the greater relative efficacy of the Idealist position in terms of both state and system level objectives. – – Die Regeln sowohl der Idealisten wie der Realisten zur Machtausübung in einem Vielstaatensystem werden beschrieben und deren Auswirkungen auf den Erhalt des internationalen Systems und staatliches Überleben untersucht. In einer experimentellen Studie werden mit Hilfe eines umfangreichen Computer-Simulationsmodells diese beiden konkurrierenden außenpolitischen Verhaltensstile untersucht. Aus den Ergebnissen geht hervor, daß der idealistische Ansatz vergleichsweise effektiver für das internationale System als auch für den Nationalstaat ist.
Keywords: 320